Influence of hybrid nano/micro particles on the mechanical performance of cross-ply carbon fibre fabric reinforced epoxy polymer composite materials - Srivastava V.K.; Quadflieg T.; Gries T. (My University, 2025)
This study presents the flexural strength, compressive strength, and impact energy behaviour of graphene nanoplates and fly ash microparticle-loaded cement-based CFRP composites manufactured by the vacuum-assisted resin infusion method (VARIM). The composite structures consist of a fixed ratio of graphene nanoplates (2%), fly ash (2%), silica (2%), cement (2%), and sand (4%) particles filled into cross-plied carbon fibre-reinforced epoxy resin polymer composite beams and columns. Composites fabricated by hand lay-up methods because of infiltration problems. A three-point bending test through the width was used to measure the flexural strength of the graphene nanoplate (GnP)-filled CFRP composite beam. The low-velocity Izod impact and Charpy impact tests through the thickness were used to determine Charpy impact energy (3.46 J), Izod impact energy (2.5 J), and the dynamic fracture toughness of notch specimens under Charpy (28.5 KJ/m2) and Izod impact (25.0 KJ/m2). Also, the compressive test method was used to measure the compressive strength of hybrid particles and short glass fibre-reinforced epoxy resin composite square and circular columns. The results show compressive strength and flexural strength. Izod impact energy, Charpy impact energy, and dynamic fracture toughness of hybrid nano/microparticle-filled fibre composites have higher values than virgin fibre composites because of the influence of graphene nanoparticles and the perfect interface bonding between two dissimilar molecules of nano and microparticles, which improve the fracture toughness and absorb impact energy. Overall, the results show that molecules of nano/microparticle-filled carbon fibre and glass fibre-reinforced epoxy resin composites can be used in seismic wave resistance because of their improved mechanical properties compared to virgin fibre composites. In addition, SEM micrographs clearly show that nano- and microparticles are resistant to crack propagation and the debonding of matrix fibres. © The Author(s) 2023.